Aplikasi Pupuk KCl dan Pupuk Kandang Ayam Terhadap Ketersediaan dan Serapan Kalium Serta PertumbuhanTanaman Jagung (Zea mays L.) Pada Tanah Inseptisol Kwala Bekala - Andri Martilova Sebayang; MMB Damanik; Kemala Sari Lubis (Jurnal Agroekoteknologi, 2015)
The study aims to determine the effect of KCl fertilizer and hen house fertilizer to potassium avaibility and absorption also the growth of maize crop (Zea mays L.) at Inceptisol soil of Kwala Bekala. This study is conducted at home gauze and also in Chemical Laboratory and Fertility of soil, Faculty of Agriculture, University of North Sumatera. Study is compiled in Random Design of Factorial Group consisting of 2 factors with restating. First factor of urea which consist of 4 dose fertilizer: 1.K0 (0), 2.K1 (0,125), 3.K2 (0,25), 4. K3(0.375) and both factor of goat house fertilizer: 1.A0 (0), 2.A1 (25), 3.A2 (50), 4. A3 (75).Result of study show application of KCl fertilizer have an effect on reality to improve the crop herght,dry weight of crop root and dry weight of crop coronet. Application of hen house fertilizer don’t have an effect in reality to improve soil pH, soil C-Organic, soil K-Total, absorbtion of K crop, height of crop, weight dry of KCl fertilizer and hen house fertilizer don’t have an effect in reality which do well by parameters.The usage of hen house fertilizerat dose 10 ton/ha instead of KCl fertilizer in maintaining soil potassium availability.Keywords: KCl fertilizer, hen house fertilizer